2017
DOI: 10.1080/00268976.2017.1294267
|View full text |Cite|
|
Sign up to set email alerts
|

Density matrix-based time-dependent configuration interaction approach to ultrafast spin-flip dynamics

Abstract: Recent developments in attosecond spectroscopy yield access to the correlated motion of electrons on their intrinsic time scales. Spin-flip dynamics is usually considered in the context of valence electronic states, where spin-orbit coupling is weak and processes related to the electron spin are usually driven by nuclear motion. However, for core-excited states, where the core hole has a nonzero angular momentum, spin-orbit coupling is strong enough to drive spin-flips on a much shorter time scale. Using densi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…For Fe 3+ , for instance, it has been found that the low‐energy part of the L 3 ‐edge is dominated by t 2 g ‐type transitions . The multiplicity of the core‐excited states strongly depends on energy . For energies up to about the L 3 maximum spin‐conserving quintet–quintet transition dominate.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Fe 3+ , for instance, it has been found that the low‐energy part of the L 3 ‐edge is dominated by t 2 g ‐type transitions . The multiplicity of the core‐excited states strongly depends on energy . For energies up to about the L 3 maximum spin‐conserving quintet–quintet transition dominate.…”
Section: Applicationsmentioning
confidence: 99%
“…Various real-time methods have been applied for simulations of the core spectra and dynamics in the core-excited states such as RT-TDDFT, [202][203][204] TD-CI, [205][206][207] non-Dyson algebraic diagrammatic construction (ADC), 208 real-time timedependent equation of motion (EOM)-CC, 209 and ρ-TD-RASCI. 198,210,211…”
Section: Time-domain Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is purely electronically driven and occurs even when the nuclei are fixed and no coupling to the vibrational bath is accounted for. 12,13 Since isolated few-femtosecond and sub-femtosecond pulses require special techniques to be obtained, 1 we have investigated what happens if pulse trains are applied. The parameter space (λ, σ, E 0 , Ω) of these pulse bursts (see Section III) has been systematically screened.…”
Section: B Multipulse Excitationmentioning
confidence: 99%
“…initiate the dynamics that are much more similar to those triggered by a single pulse. 12,13 For instance, two carrier frequencies ( Ω =708.4 and 711.5 eV) and pulse durations (σ = T /14 and σ = T /28) correspond to different yields of triplet states. However in general, one can say that dynamics driven by a series of pulses seems to be less dependent on the characteristics of a particular pulse in a train than in case of isolated pulses.…”
Section: B Multipulse Excitationmentioning
confidence: 99%